Effects of hypoxia severity on muscle oxygenation kinetics using statistical parametric mapping during repeated treadmill sprints - Hansen, C.; Brocherie, F.; Millet, G. P.; Girard, O. (International Journal of Sports Physiology and Performance, 2024)
Purpose: We examined the effects of increasing hypoxia severity on oxygenation kinetics in the vastus lateralis muscle during repeated treadmill sprints, using statistical parametric mapping (SPM).